Development of An Integrated Moodle-Based Physical Education E-learning with Religious Content on the Topic of Pencak Silat at SMA Genrus Nusantara Boarding School Kendal (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Moodle is one of the e-learning platforms that can be developed to support distance learning effectively. In order not only to function as knowledge transfer, e-learning needs to be integrated with religious content. This research aims to: (1) produce an integrated Moodle-based physical education e-learning with religious content on the topic of Pencak Silat; (2) test the feasibility; and (3) test the effectiveness of e-learning product. This Research and Development uses 3 stages of 4D model (define, design, develop). The final product is produced after passing the validation by experts and two trials. Small-scale trials were conducted on 20 students and large-scale on 73 students of class X. Data analysis include feasibility test, student responses test, effectiveness test, t-test. This study shows the following results: (1) e-learning was developed using Moodle version 3.11.6 which provides several features: virtual meeting, e-books, discussion forums, learning videos, online exams; (2) e-learning has been declared feasible based on validation of expert in the field of learning media with percentage of 93,75% with “very feasible” criteria, expert in the field of physical education with percentage of 87,50% with “very feasible” criteria, and user responses with percentage of 79,50% with “good” criteria; (3) e-learning product was proven effective based on the t-test paired samples taken from the results of the pretest and posttest.